Seebeck Coefficient of SOI Layer Induced by Phonon Transport - Salleh, Faiz; Oda, Takuro; Suzuki, Yuhei; Kamakura, Yoshinari; Ikeda, Hiroya (Makara Journal of Technology, 2015)
The Seebeck coefficient of a patterned Si wire on P-doped SOI (Si-on-insulator) layer with a carrier concentration of 1018 cm-3 was measured near room temperature. The Seebeck coefficient is found to be smaller than that in the SOI layer and to be closer to the calculated Seebeck coefficient including the electronic contribution. The decrease in the Seebeck coefficient of Si wire is likely to occur due to the elimination of the contribution of phonon drag part. From the theoretical calculation of scattering rates by considering the scattering processes in phonon system, it is considered that an increase in phonon-boundary scattering and simultaneously a decrease at the cross section of SOI layer are likely responsible for eliminating the phonon drag effect.